2007
DOI: 10.1681/asn.2007020166
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Steroids and Cyclophosphamide in Adults with Nephrotic Syndrome Caused by Idiopathic Membranous Nephropathy

Abstract: Idiopathic membranous nephropathy (IMN) is the most common cause of nephrotic syndrome in adults. Universal consensus regarding the need for and the modality of therapy has not been formed because of a lack of controlled trials of sufficient size, quality, and duration. This study compared the effect of a 6-mo course of alternating prednisolone and cyclophosphamide with supportive treatment in adults with nephrotic syndrome caused by IMN on doubling of serum creatinine, development of ESRD, and quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
234
4
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(267 citation statements)
references
References 30 publications
23
234
4
6
Order By: Relevance
“…The immunosuppressive recommendations for MGN based on RCTs include cyclophosphamide, chlorambucil, and cyclosporine regimens (5,18,(33)(34)(35). Most of these, but not all, concomitantly used corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunosuppressive recommendations for MGN based on RCTs include cyclophosphamide, chlorambucil, and cyclosporine regimens (5,18,(33)(34)(35). Most of these, but not all, concomitantly used corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…The design and conduct of therapeutic studies for treatment of MGN remains a challenge because of its relatively slow evolution and highly variable natural history. Long-term follow-up publications of randomized controlled trials (RCTs) on cytotoxic therapy have demonstrated a reduction of ESRD in some (4,5) but not all studies (6). The effect of calcineurin inhibitors on remission of proteinuria is clear, but their effect on renal survival is uncertain (7).…”
Section: Introductionmentioning
confidence: 99%
“…The decision to treat with immunosuppressive medications is complicated by the well known natural history of disease: about one-third of patients spontaneously remit, one-third remain proteinuric but with stable renal function, and one-third progress to renal failure over a period of 5 to 10 yr (1,32,33). Recent quantitative systematic reviews have found no significant difference in renal outcomes between immunosuppressive therapy, placebo, and no treatment (4,34), although these analyses antedate a recent, large randomized trial that reported significant improvement in 10-yr dialysis-free survival among patients treated with cyclophosphamide and corticosteroids (35). Speculatively, MN outcomes may not have substantially changed because alkylating agents and calcineurin inhibitors-the current therapies for patients who do not spontaneously remit or respond to RAS blockade-are nonspecific and potentially toxic.…”
Section: Discussionmentioning
confidence: 99%
“…Etiological treatments include immunosuppressive therapies such as glucocorticoids, cyclophosphamide, MMF, cyclosporin A, FK506, and azathioprine. Currently, the consistent view towards the treatment of IMN is that hormone therapy alone has a non-significant effect on IMN (Cattran et al, 1989;Beck et al, 2013), and many scholars advocate the combined use of immunosuppressant therapy (Ponticelli et al, 1998;Goumenos et al, 2006;Jha et al, 2007;Ponticelli, 2007;Dussol et al, 2008;Quaglia and Stratta, 2009;Kalliakmani et al, 2010;Polanco et al, 2010;Cattran et al, 2011;Howman et al, 2013). It is suggested that high-risk patients with deteriorated renal function should be given an active combination therapy of glucocorticoids and immunosuppressant, whereas in low-risk IMN patients, the adverse effects of glucocorticoid and immunosuppressant therapy should be avoided where possible (Quaglia and Stratta, 2009).…”
Section: Discussionmentioning
confidence: 99%